THE EFFECT OF SERVICE QUALITY AND PRICE ON CUSTOMER SATISFACTION AT TRADITIONAL MASSAGE FOR THE BLIND WITH A CERTIFICATE FROM MR. SURATNO "SUMBER HUSADA", SOUTH TANGERANG CITY - Lala Gustina; Merina Aprilia (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The aim of this research is to determine the influence of service quality and price on consumer satisfaction at a traditional massage therapist for the blind with a certificate from Mr. Suratno "Sumber Husada" South Tangerang City. The method used is a quantitative descriptive method with an associative approach. The sampling technique used is Probability Sampling, a sampling method using Slovin's theory. Data analysis uses regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that Service Quality (X1) and Price (X2) have a positive and significant effect on Consumer Satisfaction (Y) with the regression equation Y = 19.186 + 0.307 X1 + 0.121 X2. The coefficient of determination has a simultaneous effect of 14.5. Partially testing the hypothesis obtained a value of tcount>ttable or (3.762>1.291) strengthened by a value of ρvalue<Sig.0.1 or (0.000<0.1). So H0 is rejected and H1 is accepted. This means that there is a positive and significant influence between service quality and consumer satisfaction. The value obtained is tcount>ttable or (1.509>1.291) with a significance value ρvalue>Sig.0.1 or (0.135>0.1). So, H2 is rejected and H0 is accepted, this shows that there is no influence between price and consumer satisfaction. Hypothesis testing obtained a value of Fcount>Ttable or (7.865>2.36). Thus, H0 is rejected and H3 is accepted, meaning that Service Quality (X1) and Price (X2) together have a positive effect on consumer satisfaction (Y).